STANDAR PERALATAN PASTRY AND BAKERY SECTION DI HOTEL GRAND ROYAL PANGHEGAR BANDUNG - Adhitya Ryandi; Oda Oda (Jurnal Pariwisata, 2014)
Abstract - Pastry and bakery section is a section or division under the auspices  of  the   main  kitchen are responsible for handling various  events  such as hotel  weding, birthday  party, coffee break, breakfast,  lunch,  diner,  and others. The issue  will be examined how the  standard equipment  of the pastry  and bakery  section in  Hotel Grand Royal Panghegar Bandung. In terms of processing data, the authors use deskriptip analysis of  techniques of writing that tells something based on  experience  or empirical  data, which are compiled in the form of a report. Based on the observations that have been made by the author, the standard equipment of the pastry and bakery section has good and sufficient. But theem powerment  of the same  equipment  the machine is still less complete. The amount of  pastry and bakery  equipment section is adequately tailored to the capacity of event that uses the products of pastry and bakery. Pastry and bakery e quipment  conditions section is still good, but in terms of the cleanliness of the equipment is still less, so it will decrease the effectiveness of the work of the equipment. Based on data obtained by the author, the author concludes that the standard equipment is very important for the quality of the resulting product. But if  standard equipment owned less adequate, it could be addressed with mobiltas employees who have the skill and knowledge in the field of pastry and bakery. Keyword: Pastry, Bakery, Equipment, ProductsAbstrak - Pastry and bakery section merupakan section atau divisi di bawah naungan main kitchen yang bertanggung jawab menangani berbagai event-event hotel seperti weding, birthday party, coffee break, breakfast, luch, diner,dan lain-lain. Masalah yang akan diteliti yaitu bagaimana standar peralatan pastry and bakery section di Hotel Grand Royal Panghegar Bandung. Dalam hal pengolahan data, penulis menggunakan analisis deskriptip yaitu teknik penulisan yang menceritakan sesuatu berdasarkan pengalaman atau data empiris, yang disusun dalam bentuk laporan. Berdasarkan hasil observasi yang telah dilakukan oleh penulis, standar peralatan pastry and bakery section sudah baik dan memadai. Namun pemberdayaan peralatan yang berjenis mesin masih kurang lengkap. Jumlah peralatan pastry and bakery section sudah memadai yang disesuaikan dengan kapasitas event-event yang menggunakan produk-produk pastry and bakery. Kondisi peralatan pastry and bakery section masih berkondisi baik namun segi kebersihan peralatan-peralatan tersebut masih kurang sehingga akan menurunkan efektifitas kerja peralatan tersebut. Berdasarkan data yang diperoleh oleh penulis, penulis menyimpulkan bahwa standar peralatan sangat penting bagi kualitas produk yang dihasilkan. Namun apabila standar peralatan yang dimiliki kurang memadai,  hal tersebut dapat diatasi dengan mobiltas karyawan yang memiliki skill dan knowledge di bidang pastry and bakery.Kata Kunci :Pastry, Bakery, Peralatan, Produk